Pelatihan Foto Produk UMKM Teh Poci Bu Minah untuk Meningkatkan Daya Tarik Konsumen di Desa Wadungasih Sidoarjo - Milla Hariani; M Iqbal Rizqullah; Nur Aini Dian Novita (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
Product photography training is one of the important strategies in increasing consumer appeal to MSME products. This activity was carried out with the aim of helping MSME Teh Poci Bu Minah in Wadungasih Village, Sidoarjo, in developing the visual quality of its products to be more attractive and competitive in the digital market. The methods used in the training include an introduction to the basics of product photography, lighting techniques, product arrangement, and the use of simple tools such as cellphone cameras. The results of the training showed a significant increase in participants' ability to produce more professional and attractive product photos. In addition, there was an increase in consumer interest based on engagement data on social media and an increase in sales after the publication of photos that had been improved in quality. This activity is expected to be an example of MSME empowerment through increasing digital and visual literacy.